2016
DOI: 10.1007/s13197-016-2290-0
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene inhibited sprouting of potato tubers by influencing the carbohydrate metabolism pathway

Abstract: The aim of this study was to investigate the role of ethylene to control sprouting of potatoes by observing the effect of exogenous ethylene on carbohydrate metabolism and key enzymes. The initial time of potato tuber sprouting and sprouting index were recorded, and rate of respiration, total sugar, total reducing sugar, starch, fructose, glucose, sucrose and the activities of acid invertase (AI), neutral invertase (NI), sucrose synthase (SS), sucrose phosphate synthase (SPS), starch phosphorylase and amylase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…The exogenous application of GA 3 enhances the endogenous level of GAs which affects the synthesis of amylase which enhances starch break down causing quick sprout growth (Krochko et al, 1998 ; Zhang et al, 2014 ). It was suggested that in this study, the increase in sprout length in the tubers treated with 20 mgL −1 GA 3 might be due to the process of starch breakdown mediated by the enzyme, amylase (Sergeeva et al, 2012 ; Dai et al, 2016 ; Xie et al, 2018 ). In the subsequent year, the best doses of BAP and GA 3 were experimented together to determine their combined effect on dormancy period and sprout length.…”
Section: Discussionmentioning
confidence: 68%
“…The exogenous application of GA 3 enhances the endogenous level of GAs which affects the synthesis of amylase which enhances starch break down causing quick sprout growth (Krochko et al, 1998 ; Zhang et al, 2014 ). It was suggested that in this study, the increase in sprout length in the tubers treated with 20 mgL −1 GA 3 might be due to the process of starch breakdown mediated by the enzyme, amylase (Sergeeva et al, 2012 ; Dai et al, 2016 ; Xie et al, 2018 ). In the subsequent year, the best doses of BAP and GA 3 were experimented together to determine their combined effect on dormancy period and sprout length.…”
Section: Discussionmentioning
confidence: 68%
“…Endogenous ABA concentrations are very high in the dormancy period and decrease after harvest (Destefano-Baltran et al, 2006). Apart from endogenous ABA, hormones that play a role in controlling dormancy and germination are ethylene, gibberellin, cytokinins, and auxins (Tarkowska et al, 2014;Dai et al, 2016;Asalfew, 2016). Reactive oxygen species (ROS), antioxidants, and nitric oxide (NO) also play a role in controlling dormancy and sprouting in potatoes (Essid et al, 2014;Wang et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the relative content of DP 2–5 fructan first increased and then decreased during a 7-day germination period, but the content of higher DP fructans first decreased and then increased in Jerusalem artichoke tubers ( Luo et al, 2018 ). The contents of Glc, Fru, and Suc were also found to decrease in potato tubers during germination ( Dai et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The activities of VI and NI were measured as described ( Dai et al, 2016 ) with modifications. The VI activity was assayed by incubating 50 μL of crude enzyme with 50 μL of reaction buffer (0.1 M acetic acid buffer pH 5.5 and 30 mM Suc) at 30°C for 1 h. Then, 1 mL of 27.6 mM 3, 5-dinitrosalicylic acid was added and the sample was incubated in a water bath at 100°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%